2020
DOI: 10.1108/hff-07-2019-0559
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of frequency-amplitude effects of dynamic morphing for a high-lift configuration at high Reynolds number

Abstract: Purpose The purpose of this study illustrates the morphing effects around a large-scale high-lift configuration of the Airbus A320 with two elements airfoil-flap in the take-off position. The flow around the airfoil-flap and the near wake are analysed in the static case and under time-dependent vibration of the flap trailing-edge known as the dynamic morphing. Design/methodology/approach Experimental results obtained in the subsonic wind tunnel S1 of Institut de Mécanique des Fluides de Toulouse of a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The use of continuous actuation by means of morphing surfaces (e.g., [12]) or vibrating flaps (e.g., [13]) has been the subject of a few recent studies. For example, the ability of periodic surface morphing to mitigate flow separation and reduce drag at a low Reynolds number of 50,000 was demonstrated experimentally [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of continuous actuation by means of morphing surfaces (e.g., [12]) or vibrating flaps (e.g., [13]) has been the subject of a few recent studies. For example, the ability of periodic surface morphing to mitigate flow separation and reduce drag at a low Reynolds number of 50,000 was demonstrated experimentally [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of continuous actuation by means of morphing surfaces (e.g., [12]) or vibrating flaps (e.g., [13]) has been the subject of a few recent studies. For example, the ability of periodic surface morphing to mitigate flow separation and reduce drag at a low Reynolds number of 50,000 was demonstrated experimentally [12,13]. In a different experiment at a high Reynolds number of 1 million, Jodin et al [14] showed that a substantial reduction in flow instabilities could be obtained using a vibrating TEF, in addition to an increase in the aerodynamic efficiency, if the flap vibrations are set at optimal frequencies and amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…NSMB solves the Reynolds-averaged Navier Stokes equations for compressible flows on multi-block structured grids. NSMB offers all functionalities of a modern CFD code used for aerospace applications, among others, ALE (Arbitrary Lagrangian Eulerian) approach [18], turbulence models [19], chemistry modelling, grid flexibility, FSI (Fluid-Structure Interactions) coupling such as morphing wings modelling ( [20][21][22]), Chimera overlapping technique [23]. Space discretization schemes include 2nd-and 4th-order central schemes with artificial dissipation and various upwind schemes (Roe, AUSM, Van Leer ...) up to 5th order.…”
Section: A Navier Stokes Multi Block Solvermentioning
confidence: 99%
“…NSMB includes also a large variety of well tested and validated turbulence models that are standard in the aeronautical industry, like the one-equation Spalart-Allmaras [24], the Organized Eddy Simulation model [19,25], or the two-equation by Menter [26], that have been applied in the present study. Different morphing concepts are also implemented [13,[27][28][29][30] in the code. Unsteady simulations are made using the dual time stepping approach or using Newton's approach.…”
Section: A Navier Stokes Multi Block Solvermentioning
confidence: 99%
“…The SMS project has been coordinated by Institut de Mécanique des Fluides de Toulouse (IMFT). In the context of this project and at a subsonic regime, the studies [1,2] investigated the morphing through vibration and slight deformation of the near trailing edge region using piezoactuators. Actuation frequencies in the range (60Hz -400Hz) associated with low-amplitudes of deformation (order of 1mm) were examined.…”
Section: Introductionmentioning
confidence: 99%